Platelet Count/Spleen Diameter Ratio and Shear-Wave Elastography for Non-Invasive Prediction of High- Risk Varices: Can We Delay Screening Endoscopy for Compensated Cirrhosis? - ALDAĞ, BELGİN; TÜNEY, DAVUT; ÖZDOĞAN, OSMAN CAVİT (KOWSAR PUBL, 2017)
Background: Periodic Upper Gastrointestinal Endoscopy (UGIE) for Oesophageal Varices (OVs) is recommended in all compensated cirrhotic patients. The prevalence of early stage cirrhosis is on the rise with the contribution of non-invasive models for liver fibrosis. The healthcare system needs to focus on cost-effective surveillance strategies re-channelling its efforts for high-risk OVs. This study evaluated whether non-invasive means for prediction of high-risk OVs could limit UGIEs among the the Child-Pugh class A cirrhosis population. Materials and Methods: Endoscopic, clinical, and laboratory data were retrieved from medical records. Shear-Wave Elastography (SWE) and ultrasound spleen measurements, Platelet Count/Spleen Diameter (PC/SD) ratio and Child-Pugh score calculations were performed. Results: Successful elasticity acquisitions were performed in 99 cirrhosis patients. Child-Pugh score was A in 67.2% cases. The PC/SD ratios were significantly associated with high-risk (grade >= II) OVs (P = 0.002), whereas elasticity measurements were not. No significant differences were found between Child-Pugh classes for both parameters (P > 0.05). The AUROC values for the prediction of high-risk (>= grade II) OVs were moderate for PC/SD ratio (0.748), and poor for SWE (0.514). The PC/SD ratio cut-off level with best negative predictive function (93%) was 1298 to serve for excluding high-risk OVs in Child A patients. Conclusions: For compensated cirrhosis patients, the SWE was limited in accuracy to predict high-risk OVs, while PC/SD ratio appeared as a useful tool to exclude high-risk OVs giving UGIE priority to those at greatest risk for bleeding. High-quality evidence is required to delineate and prioritize endoscopy indications for Child A patients in consensus guidelines to minimize the burden from unnecessary screening UGIE procedures.
Keywords: High-Risk Esophageal Varices; Compensated Cirrhosis; Shear-Wave Elastography; Platelet Count/Spleen Diameter Ratio; LIVER STIFFNESS MEASUREMENT; SIGNIFICANT PORTAL-HYPERTENSION; ACOUSTIC RADIATION FORCE; LARGE ESOPHAGEAL-VARICES; VIRUS-RELATED CIRRHOSIS; HEPATITIS-C VIRUS; TRANSIENT ELASTOGRAPHY; ADVANCED FIBROSIS; DIAGNOSIS; SPLEEN